How do investors trade R&D-intensive Stocks? Evidence from hedge funds and other institutional investors - Alldredge, Dallin M.; Caglayan, Mustafa O.; Celiker, Umut (Journal of Banking & Finance, 2022)
We examine how institutional investors trade stocks with high research and development (R&D) expenses and investigate whether they can detect value-relevant R&D. We document significant differences between hedge funds and other institutional investors in their trading in high R&D stocks. We find that hedge funds (other institutional investors) invest more (less) in high R&D stocks compared to all other stocks. Moreover, hedge funds exhibit strong stock-picking ability in high R&D stocks, and hedge funds with larger allocations to high R&D stocks generate higher future fund returns. Our findings suggest that hedge funds have superior skill in identifying value-relevant R&D.